Multifaceted Targeting of the Chromatin Mediates Gonadotropin-Releasing Hormone Effects on Gene Expression in the Gonadotrope - Melamed, Philippa; Haj, Majd; Yosefzon, Yahav; Rudnizky, Sergei; Wijeweera, Andrea; Pnueli, Lilach; Kaplan, Ariel (Frontiers in Endocrinology, 2018)
Gonadotropin-releasing hormone (GnRH) stimulates the expression of multiple genes in the pituitary gonadotropes, most notably to induce synthesis of the gonadotropins, luteinizing hormone (LH) and follicle-stimulating hormone (FSH), but also to ensure the appropriate functioning of these cells at the center of the mammalian reproductive endocrine axis. Aside from the activation of gene-specific transcription factors, GnRH stimulates through its membrane-bound receptor, alterations in the chromatin that facilitate transcription of its target genes. These include changes in the histone and DNA modifications, nucleosome positioning and chromatin packaging at the regulatory regions of each gene. The requirements for each of these events varies according to the DNA sequence which determines the basal chromatin packaging at the regulatory regions. Despite considerable progress in this field in recent years, we are only beginning to understand some of the complexities involved in the role and regulation of this chromatin structure, including newly-described modifications, extensive cross-talk, histone variants and the actions of distal enhancers and non-coding RNAs. This short review aims to integrate the latest findings on GnRH-induced alterations in the chromatin of its target genes, which indicate multiple and diverse actions. Understanding these processes is illuminating not only in the context of the activation of these hormones during the reproductive life span, but may also reveal how aberrant epigenetic regulation of these genes leads to sub-fertility.